FEATURES OF STATE REGISTRATION OF PROPERTY RIGHTS AND BUSINESS UNDER THE CONDITIONS OF MARITAL STATE - Netska, Liubov; Damaskin, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Goal: the purpose of the article is a comprehensive legal analysis of new legislation in the field of state registration of property rights and business entities under martial law. Research methods: general (theoretical and complex) and special research methods (system-functional, formal-logical, comparative) have been utilized. Results: the researched features of state registration of property rights and business entities under martial law conditions will allow further improvement and simplification of registration procedures, identify gaps in legal regulation in state registration activities and shortcomings of current legislation. The need for drastic changes in the state registration system is proven, in particular, the exclusion of the presence of an official, both in person and virtually. It is proposed to unify the criteria by which information about property or business is provided. In order to overcome abuse or raiding, it is advisable to borrow the established practice of the European Union countries: the applicant submits a declaration (statement) about the reliability and relevance of his data. At the same time, the applicant certifies them with his electronic signature. Due to the lack of a unified approach to determining the stages of the procedure for state registration of legal entities or property rights, there is also no clear mechanism for protecting the rights of business entities whose rights are violated during state registration. In this aspect, the implementation of the decision of the subject of registration of rights and the possibility and procedure of appealing his decision are important. Discussion: correlation of laws and by-laws that regulate relations between state registration of property rights and business entities; problems of state registration of transactions under martial law; additional restrictions and prohibitions operating in the field of state registration; powers of military administrations in registration procedures; state registration of property destroyed during the war as a new need to protect violated business rights and receive appropriate compensation; ways to improve the system state registration.